RELATIVISTIC SHOCK BREAK OUT AT THE SURFACE OF HYPERNOVA STAR - Marchenko, V. V.; Hnatyk, B. I. (Одеські астрономічні публікації, 2017)
The hydrodynamics of relativistic shock break out at the surface of Hypernova star is investigated. The characteristics of hydrodynamically accelerated external layers of star (energy spectrum of accelerated particles etc.) are estimated.